Experiments with the 5G beam search in millimeter waves - raytracing and practical indoor measurements - Černý, Marek; Maršálek, Roman; Závorka, Radek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
This paper investigates the transmission characteristics of 5G signals in the millimeter-wave frequency band, focusing on indoor environments. The objective is to simulate the propagation behavior using a ray tracing approach and validate the results through experimental measurements. Simulations are conducted in Python utilizing the Sionna library, with an emphasis on channel impulse response analysis and bit error rate (BER) performance under various conditions.
Keywords: 5G; millimeter-wave; Synchronization Signal Block; Sionna; ray tracing; channel impulse response; bit error rate